Sosialisasi Pendekatan Dan Pendampingan Tentang Penambangan Masyarakat Ramah Lingkungan Di Nagari Tambang, Kecamatan IV Jurai, Kabupaten Pesisir Selatan - Nefilinda Nefilinda; Dasrizal Dasrizal; Erna Juita; Rozana Eka Putri; Momon Dt Tanamir; Shelina Rahma Putri Nst; Nova Yulfiana Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The problems faced by the people of Nagari Tambang, IV Jurai District, Pesisir Selatan Regency are: the use of natural resources in the form of mining materials is not yet environmentally friendly, the mining system is still conventional due to limited capital to carry out mining with modern tools. The service aims to socialize approaches and provide assistance regarding environmentally friendly community mining in Nagari Tambang, IV Jurai District, Pesisir Selatan Regency. The approach is related to community treatment of ex-mining land and the socialization of environmentally friendly community mining assistance regarding the processing of separating gold from other rock minerals. The strategy carried out by the service team is to minimize the impact of damage due to gold mining. The results of community service are the implementation of socialization approaches and mentoring activities in the community.